Teacher's Strategies for Increasing Students' Interest in Learning Moral Lessons - Burhanuddin Burhanuddin; Defri Ramadan; Filda Nursyda; Erika Marianti; Wulandari Safitri (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2022)
Interest in studying morals is an essential thing in the formation of the character of students. Teachers have a significant role in increasing students' interest in learning morals. This study aims to determine the teacher's strategy in increasing students' learning interest in moral lessons. This study uses a qualitative method with a case study approach. Data sources were taken from one informant through in-depth interviews. The informant is an Islamic Religious Education Teacher at senior high school 1 Pertiwi Padang. All interview results were then analyzed thematically using the Nvivo 12 qualitative analysis software. Overall the results of the analysis showed that there were two teacher strategies in increasing students' learning interest in moral lessons, namely i) Conducting direct moral coaching, ii) Motivating students. The results of this study can be used as initial data for future researchers to examine this issue in different contexts and topics